The Management of Placenta Previa with A History of Antepartum Hemorrhage: An Evidence-Based Case Report - Ayusti Anumillah, Rusyda; Dohong, Almerveldy Azaria; Bilqis, Nurdiza; Endjun, Judi Januadi (Fakultas Kedokteran, Universitas Palangka Raya, 2022)
Antepartum haemorrhage is an obstetrics emergency with significant perinatal and maternal morbidity and mortality rate. It occurs in 2-5% of pregnancies. As much as 30% of maternal deaths are caused by antepartum haemorrhage. The most common antepartum haemorrhage is placenta praevia. This case report reports a patient with a diagnosis of G4P2A1, 33 weeks gestation, with antepartum haemorrhage due to total placenta praevia, a live single-head presentation fetus. The patient reported that the vaginal bleeding was bright red, painless, moderate amount, and precipitated by intercourse. they noted moderate vaginal bleeding after intercourse. Ultrasound shows the placenta is located at the anterior corpus and expanded to the internal uterine ostium (OUI), maturation grade 1. The patient was hospitalized for observation and medication. The patient received dexamethasone 2 x 6 mg for two days and nifedipine 4 x 10 mg. If ultrasound still indicates total placenta praevia at 38-39 weeks of gestation, elective Sectio Caesarea (SC) will be scheduled. The occurrence of placenta praevia is closely associated with preterm birth and the incidence of postpartum haemorrhage as well as other complications. Therefore, it is crucial to see and anticipate the incidence of placenta praevia as early as possible based on evidence.